Significance of angiogenic factors imbalance in preeclampsia - Mateus, Julio (2015)
The role of the antiangiogenic factors, the soluble form of the fms-like tyrosine kinase receptor 1 (sFlt-1) and the soluble endoglin (sEng), in the development of preeclampsia (PE) has been demonstratedin multiple clinical and experimental studies. These studies are complemented by animal studies, inwhich overexpression of these antiangiogenic factors leads to clinical manifestations similar to PE. Although,the origin of this disease remains unknown, genetic, environmental, and immunological factorsappear to affect the normal placental development, resulting ultimately in PE. sFlt-1 and sEng inhibitthe proangiogenic properties of the vascular endothelial growth factor (VEGF) and the placental growthfactor (PlGF), affecting the normal vascular development in the placenta and the physiological vascularadaptations that occur in pregnancy. Exaggerated amounts of sFlt-1 and sEng, produced in the dysfunctionalplacenta, are released into the maternal circulation and elevated circulating concentrationsof these antiangiogenic factors are found several weeks prior to the clinical manifestations of the disease.Multiple studies have reported the capacity of circulating antiangiogenic factor concentrationsto predict PE in asymptomatic low and high risk pregnancies. The reported predictive values of sFlt-1and sEng are inconsistent across these studies and therefore their clinical use in this population is notrecommended. On the other hand, maternal plasma concentrations of these factors appear to havea better performance in women with symptoms of PE. Among the possible combinations, the ratiosof sFlt-1/PlGF, PlGF/sFlt-1, and PlGF/Engs seem to have the highest sensitivities and specificities to diagnosePE as well as the highest predictive values for PE-related adverse outcomes. These propertiessupport their clinical use in this setting and it is likely those ancillary tests will be incorporated to theclinical practice in the near future. The participation of antiangiogenic factors in the pathogenesis ofPE, also have stimulated investigation of new targeted therapies. The biological and pharmacokineticproperties of statins have converted them in one of the most promising preventive therapies forthis disease. Others are investigating agents that directly inhibit the circulating antiangiogenic factors.In-vitro and pilot clinical studies are currently evaluating the effectiveness, maternal-fetal safety, andplacental transference of these therapies.Keywords: Angiogenic factors, preeclampsia, placenta growth factor, endothelial vascular growth factor,endoglin, soluble fms-like tyrosine kinase-